Conversion motifs: a case study in Malaysia / Siti Rafidah Muhamat Dawam … [et al.] - Muhamat Dawam, Siti Rafidah; Musa, Aishah; Abdul Jalil, Muna; Ismail, Junaida (Research Management Institute (RMI), 2012)
The number of newly converts to Islam is fast growing of about 30-40% every year. This increasing number must be dealt with carefully dan taken care by the respective bodies in order to sustain the converts in Islam. This tacit knowledge of decision making process of conversion, need to be codified by gathering data on the related socio-demographic factors that have significant relationship to the conversion patterns/ motifs. This valuable knowledge needs to be shared across the related organizations dealing with the muallafs issues. In addition, this study examines the most common conversion patterns / motifs among the muallafs. The study will be conducted at the Pusat Bimbingan Saudara Baru of the Northern Region in Malaysia, particularly in Kedah, Perlis and Penang. The data collection involves a series of survey conducted among the respondents of the centres in the study. It is expected that the study could provide some insights or tacit knowledge on the sociodemographics that lead to the decision of religious conversion.